2018
DOI: 10.1080/00015458.2018.1453437
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer: factors affecting survival

Abstract: Survival outcomes in resectable GCs are affected by the experience of the surgeon and patient-related factors at the time of surgery, including tumor size, T stage, and presence of metastatic lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…Multivariate analysis showed that the depth of tumor invasion could serve as an independent prognostic factor. This conclusion was consistent with Orman's study [7].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Multivariate analysis showed that the depth of tumor invasion could serve as an independent prognostic factor. This conclusion was consistent with Orman's study [7].…”
Section: Discussionsupporting
confidence: 93%
“…5. Whereas multivariate analysis showed that these outcomes were not independent prognostic factors in GC, inconsistent with some studies [7,20,21]. The type of gastrectomy mainly depends on tumor location and size in clinical practice.…”
Section: Discussionmentioning
confidence: 78%
“…The results indicated that PVT1 overexpression is positively related with advanced invasion depth (OR = 8.77, 95% CI: 4.57‐16.85, P < 0.00001). Numerous studies reported that later TNM stage, positive vascular invasion, LNM, DM, and advanced invasion depth are all vital prognostic factors and significantly correlated with poor OS and DFS for patients . Overall, our meta‐analysis results indicated that high PVT1 expression could be an indicator of positive metastasis and poor prognosis in cancer patients.…”
Section: Discussionmentioning
confidence: 55%
“…This study found that with the increase of the T stage, all-cause mortality and GCSM increases. Recent studies have obtained similar results, and the results may be closely related to lymph node metastasis [69]. Besides, in T4, the risk of speci c death is signi cantly higher than in T1c, and the risk of death from other causes is considerably lower than in T1c.…”
Section: Discussionmentioning
confidence: 56%